2020
DOI: 10.3390/jcm9113541
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Transcutaneous Spinal Cord Stimulation on Motor Function in Chronic, Sensorimotor Incomplete Spinal Cord Injury

Abstract: Deficient ankle control after incomplete spinal cord injury (iSCI) often accentuates walking impairments. Transcutaneous electrical spinal cord stimulation (tSCS) has been shown to augment locomotor activity after iSCI, presumably due to modulation of spinal excitability. However, the effects of possible excitability modulations induced by tSCS on ankle control have not yet been assessed. This study investigated the immediate (i.e., without training) effects during single-sessions of tonic tSCS on ankle contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 82 publications
0
55
1
Order By: Relevance
“…Neural activity in spinal and possibly supra-spinal circuits [ 70 ] are caused trans-synaptically by the tonic afferent inflow. While the specific circuits recruited remain to be elucidated, they may include last-order inhibitory interneurons [ 71 ], interneurons underlying the generation of spasms [ 72 ], and those potentiating coordinated motor pattern generation [ 13 , 15 , 73 , 74 , 75 ]. To account for the carry-over effects, the triggered mechanisms must have temporarily altered the transmission through some of the circuits that were sustainedly activated for 30 min [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neural activity in spinal and possibly supra-spinal circuits [ 70 ] are caused trans-synaptically by the tonic afferent inflow. While the specific circuits recruited remain to be elucidated, they may include last-order inhibitory interneurons [ 71 ], interneurons underlying the generation of spasms [ 72 ], and those potentiating coordinated motor pattern generation [ 13 , 15 , 73 , 74 , 75 ]. To account for the carry-over effects, the triggered mechanisms must have temporarily altered the transmission through some of the circuits that were sustainedly activated for 30 min [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, across participants, the best ranked results of all walk tests, both in the evaluation of intermediate and longer-lasting effects, were achieved in individuals with severe disability related to MS. The detected statistical correlation between WISCI II scores [ 38 ] and ranked results of the walk tests may hint at the necessity for a critical residual walking ability to be present for the intervention to be effective, while WISCI II scores of 19 and 20 may leave less space for further intermediate improvement [ 15 ]. Notably, within the group of eight individuals with severe disability, WISCI II scores showed a wide range from 9 (walker and braces) to 19 (one cane).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, continuous cervical tSCS was delivered at 30 Hz with biphasic rectangular pulses of 400-µs width and stimulation intensities at a level to elicit paresthesias in the upper-limb muscles for a total duration of 10 min while participants remained in the supine position at rest. Many previous studies reporting therapeutic effects of tSCS used stimulation frequencies between 15 and 50 Hz [6,[10][11][12]15,26,28,39,40], while we used 30 Hz in the current study. We also used 400-µs pulse width, which was within the range previously utilized in neuromodulation applications.…”
Section: Continuous Cervical Tscs Parameters For Inducing Neuromodulatory Effectmentioning
confidence: 99%
“…Similarly, cervical epidural SCS has been used for promoting volitional hand function in individuals with chronic tetraplegia [5]. Consistent with epidural SCS approaches, noninvasive transcutaneous spinal cord stimulation (tSCS) has also been utilized successfully in applications for improving sensory and motor function during lower-limb voluntary movement [6] and walking using lumbar stimulation [7][8][9][10][11][12], trunk stability and standing with lower thoracic and lumbar stimulation [13,14], and gripping and upper-limb function with cervical stimulation [15][16][17][18][19]. Computer simulations and experimental studies using animal models as well as human studies have shown compelling evidence that electric impulses induced by either implanted epidural or surface non-invasive electrodes can primarily activate the afferent fibers in the posterior roots of the spinal cord [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%